The Palgrave International Handbook of Football and Politics (Springer International Publishing, 2018)
This Handbook offers an analysis of the relation between football and politics, based on over 30 case studies covering five continents. It provides a detailed picture of this relation in a wide number of European, American, African, and Asian states, as well as a comparative assessment of football in a global perspective, thus combining the general and the local. It examines themes such as the political origins of football in the studied country, the historical club rivalries, the political aspects of football as a sports spectacle, and the contemporary issues linked to the political use of football. By following the same structure with each study, the volume allows for the comparison between largely investigated cases and cases that have seldom been addressed. The Handbook will be of use particularly to students and scholars in the fields of sport studies, political scientists and sociologists, as well as cultural studies, anthropology and leisure studies.